BRD9 as a novel susceptibility gene for familial cutaneous melanoma - Ferreira, Renato Xavier Arnêdo (2022)
Cutaneous melanoma (CM) is the most lethal skin cancer, accounting for 60-75% of skin cancer-related deaths. Approximately 5-15% of CM cases occur in a familial context. Germline mutations in high/intermediate risk susceptibility genes have been associated with hereditary CM; however, most genetic causes remain undetermined. Thus, the identification of novel susceptibility genes is needed. Previously, our group identified Bromodomain containing 9 (BRD9) as a promising susceptibility gene for hereditary CM by whole exome sequencing. The main goal of this project was to investigate the BRD9 mutational profile in the Instituto Português de Oncologia de Lisboa Francisco Gentil (IPOLFG) cohort of familial CM patients and to explore the functional impact of BRD9 c.183 G>C on CM aggressiveness. Therefore, the BRD9 mutational profile was evaluated by Sanger sequencing in 72 patient samples from IPOLFG. Immune cell infiltration according to BRD9 expression, mutational status and somatic copy number alterations and the immune potential of the identified BRD9 missense single nucleotide variants (SNVs) were assessed using TIMER2.0 and NetMHCpan4.1 platforms, respectively. Furthermore, the effect of BRD9 c.183G>C on A375 melanoma cells viability, migration, and MAPK pathway activation was explored. In this study, 21 reported SNVs were identified, 8 rare and 13 polymorphisms. Rare SNVs (1 in 5’UTR, 3 intronic and 4 exonic) were classified as benign according to most pathogenicity predictors. According to TIMER2.0 analysis, BRD9 genomic changes had no impact on immune infiltration. Regarding NetMHC4.1 analysis, BRD9 c.183G>C and BRD9 c.1190T>C induce lower binding affinity of BRD9 9-mer peptides to specific MHC-I. Additionally, BRD9 c.183G>C had no effect on cell viability and migration of A375 cells and seems to slightly decrease p-ERK1/2 protein level. Here, we characterized the BRD9 mutational status of IPOLFG cohort of familial CM and verified the absence of BRD9 c.183G>C in new patients. BRD9 c.183G>C do not significant impact A375 cell aggressiveness and potentially inhibit ERK1/2 pathway activation.